HUBUNGAN ANTARA PERLAKUAN ORANGTUA DENGAN PENYESUAIAN DIRI SISWA DI SEKOLAH - Sagita, Dony Darma; Erlamsyah, Erlamsyah; Syahniar, Syahniar (Konselor, 2013)
A good treatment of parents should be able to give to their children in carrying out the development, so that children can apply the treatment was well in their environment, including the development of self-adjustment. In fact many children who can not develop a self-adjustment was well in school because it gets no better treatment than their parents. This study aims to reveal the relationship between the treatment of parents with students adjustment in the school. The type a descriptive correlational study with findings that parental treatment is quite good, the adjustment of students in the school is quite good and there is a significant relationship between parental treatment adjustment of students at the school.